EFFORTS TO IMPROVE STUDENT’S LEARNING ACHIEVEMENT THROUGH QUANTUM TEACHING METHOD ON CIVIC EDUCATION SUBJECTS IN 4TH GRADE SDN KAUNGCAANG 2 - Lasip Lasip; Rohimah Rohimah (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
AbstractThe low student academic achievement in Civic Education raises the idea that learning needs to be improved. One of them is the application of the quantum teaching method in this learning, with the expectation that students learning outcomes will continue to increase and satisfactory learning outcomes, because in this method student activities are more active. The formulations in this research are (1) How to apply the quantum teaching method to Civic Education learning in 4th grade of SDN Kaungcaang 2, (2) How to improve learning outcomes through the quantum teaching method in Civic Education subject in 4th grade elementary school, (3) the obstacles founded in quantum teaching application in Civic Education subject for 4th grade students. The author uses a qualitative descriptive analysis method. The data validity test uses the triangle technique. The results showed that based on the observations and interviews result, the quantum teaching method application could improve students’ achievement. The results of observations in the previous period were 60.00, in the first period increased to 76.00, and in the second period, the average of students increased to 86.60. This shows that 90% of students succeeded in increasing the results of Civic Education with good learning outcomes.Keyword: Quantum Teaching Method; Learning Outcomes